2014
DOI: 10.1093/sw/swu024
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of Individual and Community Factors among African American Youths in Urban Public Housing

Abstract: African American adolescents are disproportionately represented in urban public housing developments. These neighborhoods are generally characterized by high rates of poverty, crime, violence, and disorganization. Although evidence is emerging on youths in these communities, little is known about their depressive symptoms, perceived efficacy, or frequency of substance use and sex-risk behavior. Further, even less is known about their exposure to community and household violence, their parents' behavior, or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Other important factors are not in the model, such as neighborhood. Previous studies have shown that neighborhood has significant effects on adolescent development (Leventhal & Brooks-Gunn, 2000; Nebbitt, Lombe, Yu, Vaughn, & Stokes, 2012; Nebbitt et al, 2014; Sampson, 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other important factors are not in the model, such as neighborhood. Previous studies have shown that neighborhood has significant effects on adolescent development (Leventhal & Brooks-Gunn, 2000; Nebbitt, Lombe, Yu, Vaughn, & Stokes, 2012; Nebbitt et al, 2014; Sampson, 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Although previous studies have demonstrated that youths who reside in a more organized neighborhood are less likely to commit delinquent acts (Sampson, 2006) and feel safer about the community (Nebbitt, Williams, Lombe, McCoy, & Stephens, 2014), contextual factors that are more proximal to the individual often exert greater effects on adolescent development than factors at a distance. Consequently, two relatively important factors are relevant: family and individual perception.…”
Section: Introductionmentioning
confidence: 99%
“…Others develop their own instruments for specific research contexts or to assess efficacy within specific subpopulations (Gibbons & Borders, 2010). Still others utilize established instruments designed to assess self-efficacy beliefs, either generally or within specific domains (Nebbitt, Williams, Lombe, McCoy, & Stephens, 2014).…”
Section: Measuring Adolescent Self-efficacymentioning
confidence: 99%
“…US teens in low-income urban areas have been the focus of research due to experiencing high rates of poverty and violence (Nebbitt et al., 2014). Despite nationwide decrease, crime in Baltimore (the country’s second deadliest city) has increased at alarming rates.…”
Section: Current Studymentioning
confidence: 99%